New oxidovanadium(iv) complex with a BIAN ligand: synthesis, structure, redox properties and catalytic activity. (13th September 2018) - Fomenko, Iakov S.; Gushchin, Artem L.; Shul'pina, Lidia S.; Ikonnikov, Nikolay S.; Abramov, Pavel A.; Romashev, Nikolay F.; Poryvaev, Artem S.; Sheveleva, Alena M.; Bogomyakov, Artem S.; Shmelev, Nikita Y.; Fedin, Matvey V.; Shul'pin, Georgiy B.; et al.
Abstract : The combination of a new oxidovanadium(iv ) complex1 with pyrazine-2-carboxylic acid (PCA; a cocatalyst) affords a catalytic system for the efficient oxidation of saturated hydrocarbons. Abstract : Reaction of VCl3 with bis[ N -(2, 6-diisopropylphenyl)imino]acenaphthene (dpp-bian) in air afforded [VOCl2 (dpp-bian)] (1 ). The complex was characterized by IR and UV-vis spectroscopies and elemental analysis. The crystal structure of1 was determined by X-ray diffraction (XRD) analysis. The vanadium atom is in a square-pyramidal OCl2 N4 coordination environment. The cyclic voltammogram (CV) in dichloromethane reveals an irreversible oxidation process at +1.40 V ( vs. Ag/AgCl) assigned to the V(iv )/V(v ) couple, and two consecutive quasi-reversible one-electron reduction processes at −0.32 V and −1.05 V ( vs. Ag/AgCl), respectively, assigned to the bian/bian −/ ˙ and bian −/ ˙/bian 2− couples, followed by irreversible reduction at −1.6 V ( vs. Ag/AgCl). The EPR spectrum of1 in toluene shows a single 8-line signal typical for oxidovanadium(iv ) complexes with d 1 configuration. The magnetic behavior of1 confirms the presence of one unpaired electron ( μ eff (330 K) = 1.67 μ B ), and the isolation of the paramagnetic centers. Application of1 to oxidation of alkanes documented high catalytic activity under mild conditions. The kinetics and selectivity of alkane oxygenation by the1 /H2 O2 and1 /PCA/H2 O2 systems (PCA is pyrazine-2-carboxylic acid) were studied. The reaction is more efficient in the presence of PCA.